Dynamic changes in bat activity over two decades following logging, changing climate, and a severe megafire - Bradley Law; Amrit Kathuria; Traecey Brassil (Conservation Science and Practice)
Abstract Forests are important environments for echolocating bats and require careful management to balance timber harvesting with conservation. While there are many studies assessing the impacts of forestry on bats, few consider potential impacts over long periods. We use time series data of bat activity sampled periodically by ultrasonic detectors and traps over 22 years at the forest stand level to model management effects. Our study area was exposed to logging at two intervals, plus thinning of older regrowth and burning by a severe megafire (44 years after initial logging in 1976). Bat activity changed dynamically over the study and in relation to disturbance. The Black Summer fire of 2020 had the largest effect on bat activity, with all forest treatments supporting low activity 10 months post‐fire. Prior to that, unlogged coupes supported the highest activity, and this remained relatively stable over time. Coupes of old regrowth had high stem density throughout the study and supported low activity. In contrast, the open space after recent logging of previously unlogged coupes in 1999 supported higher activity than adjacent old regrowth coupes, but lower activity than unlogged coupes. Activity in recently logged coupes decreased when dense regenerating trees dominated but subsequently increased as trees grew taller and a sub‐canopy space developed. Wildfire burned the entire surrounding forest in 2020, and 10 months later, bat activity was very low. These dynamic responses highlight the importance of capturing change in communities as forest structure undergoes transformation in response to disturbance. A key implication is that activity in old regrowth coupes did not recover over the subsequent two decades and that unlogged coupes supported high activity, but these effects were less than those of the megafire. The study provides support for ongoing improvement in environmental standards in forestry over the study period, especially increased exclusion zones previously absent in 1976. Ongoing monitoring is required to assess recovery after wildfire.